Perceived Differences in Course Learning Outcomes Between Science Interns and Cooperating Teachers - Mercy Joy Mendez (SEAQIS Journal of Science Education, 2026)
This study aims to examine the differences between science interns' perceptions of their course learning outcomes and their cooperating teachers' evaluations to better understand gaps in self-assessment and inform strategies for improving teacher preparation and mentoring practices. The data for this study were collected from 228 science interns and 219 cooperating teachers from selected universities and colleges in Region XI, Philippines, through face-to-face and online surveys via Google Forms. An adapted standardised questionnaire was used to assess specific course learning outcomes, including critical thinking, communication, career and teamwork, global understanding and citizenship, and academic development and educational success. A quantitative descriptive research design was employed, and purposive sampling was used to select the respondents. Subject matter experts reviewed the questionnaire to ensure content validity, and a pilot test confirmed its reliability (Cronbach's alpha = 0.856). Data were analysed using the weighted mean and the paired t-test. Results showed that both science interns (M=4.52, SD=0.3) and their cooperating teachers (M=4.32, SD=0.43) reported high levels of attainment for the assessed learning outcomes. The paired t-test indicated a statistically significant difference between the two groups' ratings (t = 31.224, p = 0.00), with cooperating teachers' evaluations slightly lower than interns' self-assessments. These findings suggest that while interns generally perceive themselves as performing well, cooperating teachers provide a more conservative perspective. Establishing clear and consistent evaluation criteria and providing targeted feedback can help align perceptions, enhance self-awareness, and support professional development of science interns.